Motor-Neuron Pool Excitability of the Lower Leg Muscles After Acute Lateral Ankle Sprain - Klykken, Lindsey W. (National Athletic Trainers' Association, Inc, 2011)
CONTEXT: Neuromuscular deficits in leg muscles that are associated with arthrogenic muscle inhibition have been reported in people with chronic ankle instability, yet whether these neuromuscular alterations are present in individuals with acute sprains is unknown. OBJECTIVE: To compare the effect of acute lateral ankle sprain on the motor-neuron pool excitability (MNPE) of injured leg muscles with that of uninjured contralateral leg muscles and the leg muscles of healthy controls. DESIGN: Case-control study. SETTING: Laboratory. PATIENTS OR OTHER PARTICIPANTS: Ten individuals with acute ankle sprains (6 females, 4 males; age = 19.2 ± 3.8 years, height = 169.4 ± 8.5 cm, mass = 66.3 ±11.6 kg) and 10 healthy individuals (6 females, 4 males; age = 20.6 ± 4.0 years, height = 169.9 ± 10.6 cm, mass = 66.3 ± 10.2 kg) participated. INTERVENTION(S): The independent variables were group (acute ankle sprain, healthy) and limb (injured, uninjured). Separate dependent t tests were used to determine differences in MNPE between legs. MAIN OUTCOME MEASURE(S): The MNPE of the soleus, fibularis longus, and tibialis anterior was measured by the maximal Hoffmann reflex (H(max)) and maximal muscle response (M(max)) and was then normalized using the H(max):M(max) ratio. RESULTS: The soleus MNPE in the ankle-sprain group was higher in the injured limb (H(max):M(max) = 0.63; 95% confidence interval [CI], 0.46, 0.80) than in the uninjured limb (H(max):M(max) = 0.47; 95% CI, 0.08, 0.93) (t(6) = 3.62, P = .01). In the acute ankle-sprain group, tibialis anterior MNPE tended to be lower in the injured ankle (H(max):M(max) = 0.06; 95% CI, 0.01, 0.10) than in the uninjured ankle (H(max):M(max) = 0.22; 95% CI, 0.09, 0.35), but this finding was not different (t(9) = −2.01, P = .07). No differences were detected between injured (0.22; 95% CI, 0.14, 0.29) and uninjured (0.25; 95% CI, 0.12, 0.38) ankles for the fibularis longus in the ankle-sprain group (t(9) = −0.739, P = .48). We found no side-to-side differences in any muscle among the healthy group. CONCLUSIONS: Facilitated MNPE was present in the involved soleus muscle of patients with acute ankle sprains, but no differences were found in the fibularis longus or tibialis anterior muscles.